To solve the system of equations, we can use the method of substitution or elimination. I will use the method of substitution.
Step 1: Solve one equation for one variable.
Let's solve the first equation for x:
3x + 4y = 48
3x = 48 - 4y
x = (48 - 4y)/3
Step 2: Substitute the expression for x into the second equation.
6x + 2y = 60
6((48-4y)/3) + 2y = 60
Simplify:
16y/3 + 2y = 60
Step 3: Solve for y.
Multiplying the equation by 3 to get rid of the fraction:
16y + 6y = 180
22y = 180
y = 180/22
y = 90/11
Step 4: Substitute the value of y back into one of the equations to solve for x.
x = (48 - 4(90/11))/3
x = (48 - 360/11)/3
x = (528/11 - 360/11)/3
x = 168/11 / 3
x = 168/33
x = 56/11
Therefore, the solution to the system of equations is:
x = 56/11
y = 90/11
o solve this system, you could do the following steps:%0D%0A%0D%0A3x+4y=48%0D%0A3%0D%0A%0D%0A+%0D%0A4%0D%0A%0D%0A=%0D%0A48%0D%0A %0D%0A6x+2y=60
1 answer